AKIBAT HUKUM BAGI NARAPIDANA YANG MELAKUKAN TINDAK KEJAHATAN DI DALAM LEMBAGA PEMASYARAKATAN KELAS IIA KUPANG SERTA UPAYA PENANGGULANGANNYA - Hida, Dian J. A; Leo, Rudepel Petrus; Amalo, Heryanto (Petitum Law Journal, 2023)
The Criminal Code (KUHP) regulates the sanctions that will be received if a crime is committed. Persecution is regulated in Articles 351 to 356 of the Criminal Code. The provisions of these articles regulate ordinary abuse, light abuse, planned abuse, serious abuse, planned serious abuse, and abuse of people of certain qualities as well as abuse in the form of participating in attacks or fights. regarding abuse between prisoners, especially in relation to legal sanctions, the author is interested in studying this matter more by conducting research for writing a thesis entitled "Legal Consequences for Prisoners Who Commit Crimes in the Kupang Class IIA Penitentiary and Efforts to Overcome Them." This research is empirical juridical legal research with the approach method used in this research, namely: (1) Empirical legal research (empirical juridical) (2) This research uses a case approach. The results of this research show that: (1) Every violation of order committed by a prisoner will be resolved first through a mediation process. However, if the impact of the fight results in serious injuries, the prison officers will hand them over to the authorities. The punishments or sanctions given by Prison Officers to Prisoners who violate the provisions of the regulations in force in correctional institutions: Providing warnings or warnings to Prisoners if the violation is considered a minor violation, Throwing each Prisoner whose violation is considered a serious violation into solitary confinement, Does not grant remission or conditional release to any prisoner who has repeatedly committed violations. (2) Efforts to overcome criminal acts in prisons are Preventive Efforts (Socializing Human Rights values, Providing a sense of justice to all prisoners, Increasing Supervision of Correctional Institutions) and Repressive Efforts (imposing sanctions in the form of disciplinary action by placing them in seclusion cells and being quarantined according to the specified time or other sanctions determined by prison regulations.